15-O-Acetyl-3-O-benzoylcharaciol and helioscopinolide A, two diterpenes isolated from Euphorbia helioscopia suppress microglia activation. (26th January 2016) - Wang, Hao; Liu, Yu; Zhang, Jingling; Xu, Jing; Cui, Chun-Ai; Guo, Yuanqiang; Jin, Da-Qing
Highlights: Two deterpenes in Euphorbia helioscopia inhibit NO, PGE2, ROS and cytokines production. The deterpenes suppressed iNOS and COX-2 expression. The deterpenes inhibit NF-κB but not Akt and MAPK pathway. The deterpenes exhibited strong affinity to both iNOS and COX2 in AutoDock 4.2 analysis. Abstract: Microglia activation plays an important role in the pathogenesis of various neurodegenerative diseases by producing neurotoxic factors. In the present study, we found that two diterpenes isolated from Euphorbia helioscopia, 15-O-Acetyl-3-O-benzoylcharaciol and helioscopinolide A suppressed NO and PGE2 production by inhibition of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) expression in lipopolysaccharide (LPS)-stimulated BV2 microglia cells. The diterpenes also inhibited the production of ROS and proinflammatory cytokines including interleukin (IL)-1β, IL-6 and tumor necrosis factor (TNF)-α, the mechanism involved the NF-κB but not Akt and mitogen-activated protein kinase (MAPK) pathway. Moreover, the two diterpenes also attenuate microglia activation-mediated neuronal death. These results suggest that 15-O-Acetyl-3-O-benzoylcharaciol and helioscopinolide A may provide potential therapeutic strategy for various neuroinflammatory diseases.